Assessing Science Training Programs: Structured Undergraduate Research Programs Make a Difference. (13th June 2018) - Wilson, Alan E; Pollock, Jenna L; Billick, Ian; Domingo, Carmen; Fernandez-Figueroa, Edna G; Nagy, Eric S; Steury, Todd D; Summers, Adam
Abstract: Training in science, technology, engineering, and mathematics (STEM) is a top priority for driving economic growth and maintaining technological competitiveness. We propose that exposure to a rigorous research program as an undergraduate leads to success in a research STEM career. We compared the scientific outcomes of 88 participants from five National Science Foundation Research Experiences for Undergraduates (REU) Site programs with demographically similar applicants to assess the impact that formal, organized, and funded undergraduate summer research experiences have on participants. Our study demonstrates that REU participants are more likely to pursue a PhD program and generate significantly more valued products, including presentations, publications, and awards, when compared with applicants. We believe that key components of the program include funding for personal and professional needs; access to diverse intellectual, analytical, and field resources; and the presence of other undergraduate researchers who support each other and share their goals and interests.